A Novel Mannich Based Metal II Complexes: Synthesis and Characterization of Magnetic, Conductivity and Antimicrobial Properties - Ramasamy, M.; Velayutham, G.; Pitchaipillai, R. (Karagandy University of the name of academician E.A. Buketov, 2025)
A novel Mannich base (2R,9R)-2-((S)-((2-aminoethyl)amino)(2-hydroxyphenyl)methyl)-6-hydroxy-9 phenyl-2,3,4,9-tetrahydro-1H-xanthen-1-one (LI), composed from xanthene, salicylaldehyde, and ethylenedi amine, was employed to synthesize unique complexes of Ni(II), Mn(II), Cr(II), Co(II), and Cu(II). The struc tural characteristics of the complexes were determined by studying microanalytical findings and using analyt ical methods such as EPR, FT-IR, 1H & 13C NMR, and UV-visible spectroscopy. The electronic spectra of the complexes suggested that the metal ion is fenced with octahedral structure. The molar conductivity of the metal chelates in DMSO was shown in the range of 18–28 Ω–1mol–1cm2. The EPR studies of the copper com plex dissolved in dimethyl sulfoxide (DMSO) was obtained at temperature of 300 K, and its unique character istics were analysed. The antimicrobial potential of the ligand and its complexes has been thoroughly exam ined towards K. pneumaniae, S. aureus, P. aeruginosa, E. coli, C. albicans, C. neoformans, M. audouinii, A. niger microorganisms. Experimental results have demonstrated that all of the complexes exhibit substantial antimicrobial action when related to both the unbound ligand and the standard. Furthermore, the validity of the biological research was verified through molecular docking antifungal and antibacterial tests. Overall, the obtained results confirm the multidirectional antimicrobial efficacy of the new Mannich base complexes and demonstrate their high pharmaceutical potential for further studies.
Keywords: Antimicrobial activity; Docking; Grindstone; Ligands; Mannich base; Metal complexes; Xanthene